Family case of cardiac achalasia - Yu. V. Yevsyutina; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To present modern data on the genetic theory of development of cardiac achalasia and data of original clinical case of the patient with vertical type of achalasia inheritance.Key points. Cardiac achalasia is idiopathic disease, caused by inflammation and degeneration of myenteric plexus resulting in loss of postganglionic inhibitory neurons, essential for relaxation of the lower esophageal sphincter and peristaltic contractions of the esophagus. Main symptoms of achalasia are: dysphagia, regurgitation, chest pain and weight loss. Nowadays there are three main etiological hypotheses in cardiac achalasia development — genetic, infectious and autoimmune. Genetic theory is one of most widely discussed concepts.Conclusion. Presented clinical case illustrates genetic theory of cardiac achalasia development in 81 year-old mother and 58 year-old daughter. Genetic analysis which is broadly applied for patients with achalasia, has allowed to come around to disease etiology, anyhow additional investigations in this area are necessary.